Components of responsibility in estimating relative value units: How do dentists value their work?. Issue 4 (26th April 2018) - Brennan, DS; Ju, X; Teusner, DN
Abstract: Objectives: Responsibility weights can translate services into a common scale of work effort (relative value units). The aims were to describe the responsibility weights for main areas of dental services and assess associations of ratings of the importance of the components of responsibility with responsibility weights. Methods: Mailed questionnaires were used to collect responsibility weights and components of responsibility from a random sample of Australian dentists who were randomly assigned into panels. Across the panels, weights were elicited for 299 service items from 9 service areas. Data were weighted to the age and sex distribution of the workforce. Ordered logit regression models assessed differences in weights by ratings of importance of the 8 components of responsibility. Results: Responses were collected from 846 dentists (response rate = 37%). Adjusted models showed that, with the exception of general/miscellaneous services, all remaining service areas were associated with between 3 and 7 components. Preventive weights were associated with dexterity and mental effort but negatively with perception. Diagnostic weights were associated with knowledge, judgement, experience, perception, physical and mental effort, and negatively with dexterity. Ratings of components of responsibility were associated with responsibility weights and showed varying patterns across service areas. Mental effort, invasiveness, dexterity, experience and knowledge were associated with responsibility weights in the majority of service areas. Conclusions: The observed variation in weights across service areas showed that dentists discriminated between services in a systematic and cognizant manner and so provided broad validation of weights assigned by dentists.